Comparative judicial review - Delaney, Erin F.; Dixon, Rosalind (Chltenham, UK ; Northampton, Mass : Edward Elgar Publishing, 2018)
"Constitutional courts around the world play an increasingly central role in day-to-day democratic governance. Yet scholars have only recently begun to develop the interdisciplinary analysis needed to understand this shift in the relationship of constitutional law to politics. This edited volume brings together leading scholars of constitutional law and politics to provide a comprehensive overview of judicial review, covering theories of its creation, mechanisms of its constraint, and its comparative applications, including theories of interpretation and doctrinal developments."--
Introduction / Erin F. Delaney and Rosalind Dixon -- The real case for judicial review / Alon Harel and Adam Shinar -- Constitutions as political insurance : variants and limits / Rosalind Dixon and Tom Ginsburg -- Comparative constitutional law as a window on democratic institutions / Samuel Issacharoff -- The origins and growth of judicial enforcement / Steven Gow Calabresi -- Interpreting constitutions in divided societies / Hannah Lerner -- Judicial review in the context of constitutional Islam / Salma Waheedi and Kristen Stilt -- New judicial roles in governance / Robert A. Kagan, Diana Kapiszewski and Gordon Silverstein -- Competition or collaboration : constitutional review by multiple final courts / Wen-Chen Chang and Yi-Li Lee -- Judicial review as a self-stabilizing constitutional mechanism / Tonja Jacobi, Sonia Mittal and Barry R. Weingast -- Losing faith in law's autonomy : a comparative analysis / Theunis Roux -- Courts and support structures : beyond the classic narrative / David Landau -- National perspectives on international constitutional review : diverging optics / Karen J. Alter -- Efficacious judging on apex courts / Lee Epstein and Jack Knight -- Limiting judicial discretion / Mila Versteeg and Emily Zackin -- Beyond Europe and the United States : the wide world of judicial review / Virgílio Afonso da Silva -- Judicial review and public reason / Wojciech Sadurski -- Pockets of proportionality : choice and necessity, doctrine and principle / Vicki C. Jackson -- Comparative approaches to constitutional theory / Jamal Greene and Yvonne Tew -- Judicial review and the politics of comparative citations : theory, evidence and methodological challenges / Ran Hirschl.
Includes bibliographical references and index.
Keywords: Constitutional law; Constitutional law; Judicial review; Judicial review